Enhanced chirality in a dielectric metasurface without breaking symmetry. Issue 3 (22nd December 2022) - Liu, Xingguang; Li, Junqing; Zhao, Rui; Zhang, Yingjie; Dong, Yongkang
Abstract : The proposed dielectric metasurface supports the excitation of bound states in the continuum. After introducing chiral enantiomers with weak chirality into the surrounding medium, the chiroptical effect of the metasurface can be greatly enhanced. Abstract : We propose a dielectric metasurface constructed by quadrumer silicon nano-disks with crossed slots in the middle. This metasurface can support the excitation of bound states in the continuum which are closely related to the toroidal dipole resonance. After introducing chiral enantiomers with weak chirality into the surrounding medium, due to the bound states in the continuum, the chiroptical effect of the metasurface can be greatly enhanced. In particular, this metasurface breaks neither the in-plane nor out-plane symmetry, which has lower requirements of spatial processing capabilities. The proposed metasurface can be used in the trace analysis of chiral enantiomers and may lead to potential applications for tailored phase control and ultra-integrated molar chiral sensing metadevices.